Effect of sono-guided fascia iliaca block versus spinal anesthesia on tourniquet pain during foot and ankle orthopedic surgery - Mosaffa , Faramarz; Dabir , Shideh; Tavakoli , Nima; Hosseini , Behnam; Sabaghzadeh , Amir (Researcher Bulletin of Medical Sciences, 2020)
Introduction: The pneumatic thigh tourniquets are routinely used in below knee orthopedic surgeries to provide a bloodless operative field. Moderate to severe thigh pain following tourniquet inflation is a common patient complaint that can be so severe that necessitate general anesthesia. In the present study, we assessed the effectiveness of a single dose fascia iliaca block on thigh tourniquet pain during unilateral orthopedic foot and ankle surgery performed under popliteal sciatic nerve block. Materials and Methods: Seventy-two American Society of Anesthesiologists physical status 1 or 2 patients were randomly divided into two equal groups of spinal anesthesia and fascia iliaca block. Spinal anesthesia was provided with 15 mg of 0.5% hyperbaric bupivacaine. Fascia iliaca and popliteal blocks were performed under the guidance of ultrasound using 30 ml of 1.5% lidocaine and 20 ml of lidocaine 1.5% with epinephrine 1:200000, respectively. Results: Intraoperative tourniquet pain and the use of analgesics were significantly higher and patient satisfaction was significantly lower in the fascia iliaca block group than in the spinal anesthesia group. Conclusion: Fascia iliaca block alone was inadequate for relieving thigh tourniquet pain during surgery. However, for patients who are not suitable for spinal or general anesthesia, it can be used with supplementary intravenous analgesia for tolerance of thigh tourniquet in foot and ankle surgeries performing under popliteal sciatic nerve block.